2020
DOI: 10.1021/acs.jafc.9b04957
|View full text |Cite
|
Sign up to set email alerts
|

Food-Grade Emulsions and Emulsion Gels Prepared by Soy Protein–Pectin Complex Nanoparticles and Glycyrrhizic Acid Nanofibrils

Abstract: Glycyrrhizic acid (GA) and GA nanofibrils (GN) have been shown to be efficient natural emulsifiers for formation and stabilization of food emulsions. In this work, the emulsion properties of GN in the presence of soy protein isolate−pectin complex nanoparticles (SPNPs) were studied to understand the impact of the nanofibril−nanoparticle interactions on emulsion stabilization. In the presence of low GN concentrations (0.1−0.5 wt %), the synergy in reducing the interfacial tension was observed due to SPNPs−GN co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 59 publications
2
32
0
Order By: Relevance
“…When the concentration of LAE was between 0.0075% and 0.02%, the three-phase contact angle of the LAE/NMMT complex was approximately 90˚, which indicated that the LAE/NMMT complex had stronger amphiphilic property and better emulsifying ability. It was consistent with the microscopic observation [24]. The oil-water contact angle, measured through water in the oil phase having strong polarity, was larger, and the particles combined more easily at the oil-water interface, which was beneficial to the formation and stability of oil-in-water Pickering emulsions [25].…”
Section: Pickering Emulsion Stabilised By Lae/nmmtsupporting
confidence: 89%
“…When the concentration of LAE was between 0.0075% and 0.02%, the three-phase contact angle of the LAE/NMMT complex was approximately 90˚, which indicated that the LAE/NMMT complex had stronger amphiphilic property and better emulsifying ability. It was consistent with the microscopic observation [24]. The oil-water contact angle, measured through water in the oil phase having strong polarity, was larger, and the particles combined more easily at the oil-water interface, which was beneficial to the formation and stability of oil-in-water Pickering emulsions [25].…”
Section: Pickering Emulsion Stabilised By Lae/nmmtsupporting
confidence: 89%
“…A prerequisite for a qualified stabilizer of Pickering emulsion systems is the partial wettability in both oil and water phases. The wettability of OVT fibrils/spheres in oil and water phases was reflected by a three-phase contact angle (oil–water-solid) to verify if it was a qualified stabilizer of OPEs [ 36 ]. Figure 2 shows that the three-phase contact angles of OVT fibrils and OVT spheres were 84.8° and 80.2°, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The self-assembling of GLR into a fibrillar network leads to the formation of micro-structures (Fig. 4) with specific mechanical properties (Li et al, 2020;Wan et al, 2018). The self-assembly of supramolecular GLR nanofibrils can be exploited to form ultrastable, thermostimulable, and processable foams (Ma et al, 2019).…”
Section: Improved Glr Formulation For In Vivo Administrationsmentioning
confidence: 99%